Avaliação histomor fométrica dos efeitos da movimentação dentária induzida sobre molares murinos submetidos à luxação extrusiva em períodos tardios - Lelis, Éverton Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The repair process after dentoalveolar trauma (DT) depends on several factors and complications may arise weeks, months or even years after the injury, it is essential for long-term monitoring. Therefore orthodontic approach teeth related episodes of DT greatest concern and requires careful management. The objective of this study was to evaluate root resorptions on traumatized teeth - extrusive luxation (EL), submitted to induced tooth movement (ITM) after later periods of tissue repair. Eighty young male Wistar rats aged 45 days were used in the present study. The animals were divided into eight groups (n = 10): Group 1 (G1) sacrificed 28 days after, without EL and ITM; Group 2 (G2) subjected to EL and sacrificed 28 days after; Group 3 (G3), 28 days after were submitted to a ITM during 7 days and sacrificed; Group 4 (G4) subjected to EL and, 28 days after, ITM during 7 days and sacrificed. Group 5 (G5) sacrificed 45 days after, without EL and ITM; Group 6 (G6) subjected to EL and sacrificed 45 days after; Group 7 (G7), 45 days after were submitted to a ITM during 7 days and sacrificed; Group 8 (G8) subjected to EL and, 45 days after, ITM during 7 days and sacrificed. The tooth used for the procedures was first upper right molar, luxated using Hollemback 3S and moved mesially by nickel-titanium closed coil (50 cN). After the experimental period, the animals were sacrificed by anesthetic overdose and the right maxilla were removed and processed in longitudinal sections stained with hematoxylin and eosin for histological analysis under light microscopy. Analysis of depth of root resorption by means of scores and analysis of resorptive activity through clastic cell count in contact with the radicular dentin was performed. Kappa test was used for intra-examiner reliability with a 95% confidence interval. Reliability results for...

O processo de reparo após traumatismo dentoalveolar (TD) depende de vários fatores e as complicações podem surgir semanas, meses ou até mesmo anos após a injúria, sendo indispensável o acompanhamento em longo prazo. Por esse motivo a abordagem ortodôntica de dentes relacionados com episódios de TD causa maior preocupação e requer conduta cautelosa. O objetivo deste trabalho foi avaliar as reabsorções radiculares em dentes com TD do tipo luxação extrusiva (LE) submetidos à movimentação dentária induzida (MDI) após tempos tardios de reparo (28 e 45 dias). Foram utilizados 80 ratos machos jovens com 45 dias de idade da linhagem Wistar. Os animais foram divididos em oito grupos (n = 10): Grupo 1, eutanasiados após 28 dias; Grupo 2, submetidos à LE e eutanasiados após 28 dias; Grupo 3, após 28 dias foram submetidos à MDI durante 7 dias e eutanasiados; Grupo 4, submetidos à LE e após 28 dias foram submetidos à MDI durante 7 dias e eutanasiados; Grupo 5, eutanasiados após 45 dias; Grupo 6, submetidos à LE e eutanasiados após 45 dias; Grupo 7, após 45 dias foram submetidos à MDI durante 7 dias e eutanasiados; Grupo 8, submetidos à LE e após 45 dias foram submetidos à MDI durante 7 dias e eutanasiados. O dente utilizado para os procedimentos foi o primeiro molar superior direito, luxado utilizando-se espátula Hollemback 3S e movimentado mesialmente por meio de mola fechada de níquel-titânio (50cN). Após tempo experimental, os animais foram eutanasiados por excesso de anestésico e a hemimaxila direita foi removida e processada em cortes longitudinais, corados em hematoxilina e eosina, para análise histológica em microscópio óptico. Foi realizada análise da profundidade das reabsorções radiculares por meio de escores e análise da atividade reabsortiva por meio de contagem de células clásticas em contato...
Keywords: Traumatismos dentários; Movimentação dentária; Reabsorção da raiz; Tooth injuries